Effect of airflow angle on abaxial surface deposition in air-assisted spraying - Xu, Shaoqing; Wang, Xiang; Li, Chao; Ran, Xiangkai; Zhong, Yuan; Jin, Ye; Song, Jianli (Frontiers in Plant Science, 2023)
Air-assisted sprayers are widely used in orchards for pest and disease control. However, air-assisted spray deposition on the abaxial surface of leaves is often limited. In this study, a method to achieve satisfactory spray deposition on the abaxial leaf surface and an assessment of factors that affect abaxial surface deposition were investigated. The effects of leaf angle, wind speed, platform velocity, and nozzle type were assessed. Abaxial surface coverage was significantly affected by leaf angle, wind speed, and nozzle type, of which the leaf angle had the strongest impact. The leaf angle largely determines the abaxial surface area exposed to the wind field. When the abaxial surface is situated leeward, deposition of droplets on the abaxial surface is difficult. Therefore, to improve abaxial surface exposure for field application, the exposure probability of the abaxial surface at different angles between the leaf and the airflow (α) was examined. The relationship was well represented by a logistic growth curve. The exposure probability exceeded 95% when the α value was greater than 5°. The latter finding was verified by conducting a field application in which the deposition efficiency on the abaxial surface (DEAS) was calculated. Adjustment of the airflow angle based on the theoretical value achieved DEAS of 49.9% and 109.3% in the middle and upper layers of the canopy, respectively, whereas the DEAS was less than 30% if the airflow angle was not adjusted. This is caused by the difference in the exposure probability of the back of the leaf. The results provide a reference for adjustment of the wind field of air-assisted sprayers in field applications.